COVID-19 and food security in Sub-Saharan Africa: Implications of lockdown during agricultural planting seasons - Ayanlade, Ayansina; Radeny, Maren A.O. (Springer, 2020)
COVID-19 pandemic movement restrictions as part of the control measures put in place by countries in Sub-Saharan Africa (SSA) has implications on food security, as movement restrictions coincided with planting periods for most of the staple crops. The measures are affecting important staple crops in SSA, and are likely to exacerbate food security challenges in many countries. Achieving adequate food supply in SSA requires developing better policies and packages to confronting the challenge of reducing hunger post COVID-19 pandemic. The lessons learned after COVID-19 crisis will be very important for African countries to rethink their strategies and policies for sustainable economic growth, as COVID-19 many have signiﬁcant impacts on all sectors of their economies.